A Recombinant DNA Technique in The Genetic Engineering of Insulin from Bacteria - Sanely; Defa Pratama; Ziske Maritska; rahman, Khaidir Yusuf (Jurnal Riset Kedokteran, 2023)
Abstract. Human Growth and human insulin were the first proteins to be produced on an industrial scale. Methods: The research method used in this study was a clinical literature review on recombinant DNA techniques from insulin in bacteria from the review literature taken from Pubmed and SCopus, for further search and analysis with other existing research. Recombinant DNA technology comprises altering genetic material outside an organism to obtain enhanced and desired characteristics in living organisms or as their products. Two biosynthetic insulin analogs have sufficiently long duration of action for use as once-daily basal insulins. Some biosimilars have been developed to human insulins as produced by Lilly and NovoNordisk, but their use is more restricted given the problems encountered by the use of human insulin, see Dolinar et al for a recent review of the field. Several companies have developed or are developing depot preparations that can be administered one a week instead of once a day. Recombinant DNA technology is an important development in science that has made the human life much easier. The clinical effect of Growth hormone therapy in children can be best measured on an annual basis and compared with predicted adult height whereas failure to lower blood sugar can be seen immediately in insulin or insulin analogue therapy. Abstrak. Pertumbuhan Manusia dan insulin manusia adalah protein pertama yang diproduksi dalam skala industri. Metode penelitian yang digunakan dalam penelitian ini adalah tinjauan literatur klinis mengenai teknik DNA rekombinan dari insulin pada bakteri dari tinjauan literatur yang diambil dari Pubmed dan SCopus, untuk selanjutnya dicari dan dianalisis dengan penelitian lain yang sudah ada. Teknologi DNA rekombinan terdiri dari pengubahan materi genetik di luar suatu organisme untuk memperoleh karakteristik yang ditingkatkan dan diinginkan pada organisme hidup atau sebagai produknya. Dua analog insulin biosintetik mempunyai durasi kerja yang cukup lama untuk digunakan sebagai insulin basal sekali sehari. Beberapa biosimilar telah dikembangkan untuk insulin manusia seperti yang diproduksi oleh Lilly dan NovoNordisk, namun penggunaannya lebih dibatasi mengingat permasalahan yang dihadapi dalam penggunaan insulin manusia, lihat Dolinar dkk untuk tinjauan terbaru di lapangan. Beberapa perusahaan telah mengembangkan atau sedang mengembangkan persiapan depot yang dapat diberikan satu kali dalam seminggu, bukan sekali sehari. Teknologi DNA rekombinan merupakan perkembangan penting dalam ilmu pengetahuan yang telah membuat hidup manusia lebih mudah. Efek klinis terapi hormon pertumbuhan pada anak-anak paling baik diukur setiap tahun dan dibandingkan dengan prediksi tinggi badan orang dewasa, sedangkan kegagalan menurunkan gula darah dapat langsung terlihat pada terapi insulin atau analog insulin.